Perovskite solar cell based on pentafluorophenol acrylate modification and preparation method thereof
By using pentafluorophenol acrylate modification technology in perovskite solar cells, a polymeric crosslinking network is formed, which solves the problems of unstable performance of perovskite solar cells and lead ion leakage in bad weather, and achieves the effect of improving photoelectric conversion efficiency and environmental friendliness.
Patent Information
- Application Number
- CN202510076889.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-18
AI Technical Summary
Perovskite solar cells are susceptible to severe weather during use, and due to the leakage of water-soluble lead ions, their performance stability is limited, which poses a potential threat to ecosystems and human health.
A perovskite solar cell based on pentafluorophenol acrylate modification was used to coat and anneale the modified solution composed of pentafluorophenol acrylate, azobisisobutyronitrile and antisolvent to the perovskite absorbing layer for coating and annealing treatment, and a polymerized crosslinking network was formed to passivate the defects of perovskite and prevent the leakage of lead ions.
It improves the quality of perovskite film and the photoelectric conversion efficiency, reduces the non-radiative recombination of carriers, promotes the extraction and transmission of carriers, and effectively prevents the leakage of lead ions, improving the stability and environmental friendliness of the device.
Smart Images

Figure CN119855364A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of novel photovoltaic materials, and in particular to a perovskite solar cell modified based on organic small molecule pentafluorophenol acrylate and a preparation method thereof. Background Art
[0002] With the depletion and pollution of fossil energy, new photovoltaic devices have attracted widespread attention. As an emerging photovoltaic technology, perovskite solar cells have broad application prospects due to their excellent photovoltaic performance and low manufacturing cost. From 2009 to now, the efficiency of perovskite cells has also increased from 3.2% to 26.7%. This increase in efficiency can be attributed to the excellent properties of perovskite materials, such as high light absorption coefficient, long charge diffusion length and adjustable band gap. 2+ Ions are a type of Lewis acid. Some researchers have proposed using Lewis bases to modify the interface. For example, CN202310550631.X discloses an organic compound-modified trans-perovskite solar cell and a method for preparing the same. 1-amino-1H-imidazole-2(3h)-thione or 2-amino-5-methyl-1,3,4-thiadiazole Lewis base organic compounds are used for interface modification. The crystallization rate and size of the perovskite crystals are controlled by controlling the time and temperature of the perovskite layer annealing treatment, thereby improving the charge transfer performance of the perovskite film. Although the photovoltaic performance has been improved to a certain extent, there are still some challenges that hinder the practical application of perovskite batteries. For example, PSCs often encounter bad weather during use. Rain and high temperature can damage PSCs. The most worrying thing is that the water-soluble heavy metal lead ions (Pb 2 + ) causes pollution to the ecosystem. It is worth noting that once lead ions enter the human body, they will cause damage to tissues and the nervous system. Therefore, the essential problem is that on the basis of ensuring its photoelectric conversion efficiency, there is a problem of limited performance stability caused by the leakage of water-soluble lead ions. Therefore, it is necessary to develop a perovskite solar cell modified with organic small molecule pentafluorophenol acrylate and its preparation method, which is of great significance to the improvement of the photoelectric conversion efficiency of solar cells and environmental friendliness. Summary of the invention
[0003] In view of this, the present invention provides a perovskite solar cell modified with pentafluorophenol acrylate to solve the problem of poor performance stability caused by lead ion leakage.
[0004] On the one hand, the present invention adopts a perovskite solar cell modified by pentafluorophenol acrylate, comprising a fluorinated conductive glass substrate, an electron transport layer, a perovskite light absorbing layer, a hole transport layer and a metal electrode stacked in sequence, wherein the perovskite light absorbing layer is coated with a modified solution containing pentafluorophenol acrylate, azobisisobutyronitrile and an anti-solvent and annealed.
[0005] Preferably, the concentration of pentafluorophenol ester in the modified solution is 3 mg / mL.
[0006] Preferably, the anti-solvent is one of chlorobenzene, isopropanol and ethyl acetate.
[0007] Another aspect of the present invention provides a method for preparing a perovskite solar cell modified with pentafluorophenol acrylate, characterized in that it comprises the following steps:
[0008] (1) Preparation of fluorinated conductive glass substrate: A FTO glass substrate was cleaned with detergent, deionized water, acetone and isopropanol in sequence, then dried and treated with ozone;
[0009] (2) Preparation of electron transport layer: coating a SnO2 precursor solution on a FTO glass substrate and annealing;
[0010] (3) Perovskite light-absorbing layer: a perovskite precursor solution prepared with lead halide, formamidine hydroiodide and methyl ammonium bromide is spin-coated on the electron transport layer, and then a modified solution prepared with pentafluorophenol acrylate, azobisisobutyronitrile and anti-solvent is dropped in for spin-coating deposition to form a perovskite light-absorbing layer;
[0011] (4) Hole transport layer: A 2,2',7,7'-tetrakis[n,n-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene solution is deposited on the perovskite light absorbing layer to obtain a hole transport layer.
[0012] (5) Metal electrode: Au electrode with a thickness of 80-100 nm.
[0013] Preferably, the lead halide includes at least one of lead iodide and lead bromide.
[0014] Preferably, step (3) is specifically as follows: 548.6 mg of lead iodide, 77.07 mg of lead bromide, 190.12 mg of formamidine hydroiodide and 21.84 mg of methyl ammonium bromide are weighed and dissolved in DMF / DMSO to prepare a precursor solution, and then 34 μL of a 519 mg / mL CsI solution is added and stirred for 2 hours to obtain a perovskite precursor solution, and 60 μL of the perovskite precursor solution is coated on the SnO2 film in two steps, the first step is to spin coat at a speed of 2200 rpm / min for 10 seconds, and the second step is to coat at a speed of 4500 rpm / min for 45 seconds, and 15 seconds before the end of the second step of spin coating, 200 μL of a modified solution prepared by 3 mg of pentafluorophenol acrylate, 0.15 mg of azobisisobutyronitrile and 1 mL of chlorobenzene is dripped on the film, and annealed at 110°C for 60 minutes to obtain a perovskite light absorbing layer.
[0015] Preferably, step (3) is specifically as follows: 1.5 mmol PbI2, 1.5 mmol formamidine hydroiodide and 0.525 mmol methyl ammonium chloride are dissolved in a mixed solution of DMF:DMSO to obtain a perovskite precursor solution, and then 60 μL of the perovskite precursor solution is coated on the SnO2 film in two steps, the first step is to spin coat at a speed of 2200 rpm / min for 10 s, and the second step is to coat at a speed of 4500 rpm / min for 45 s, and in the last 10 s of the second step, 200 μL of a modified solution prepared by 3 mg pentafluorophenol acrylate, 0.15 mg azobisisobutyronitrile and 1 mL chlorobenzene is spin-coated and dropped on the film, and the film is first annealed at 150°C for 10 min, and then annealed at 100°C for 10 min to obtain a perovskite titanium light absorbing layer.
[0016] The preparation method of the perovskite solar cell based on pentafluorophenol acrylate modified by the present invention has a simple process. In the heat treatment process, pentafluorophenol acrylate and azobisisobutyronitrile initiator are used to act together to cause in-situ self-polymerization. Not only the formed polymer film passivates the defects of the perovskite, improves the quality of the perovskite film, and effectively reduces the non-radiative recombination of carriers, but also promotes the extraction and transmission of carriers, thereby improving its photoelectric conversion efficiency (from 19.32% to 22.73%; from 21.19% to 24.53%); and forms a polymer cross-linked network wrapped on the perovskite grain boundary. In the process of perovskite crystal growth, C=O in the molecule and uncoordinated Pb 2+ Combined with other materials, it can effectively prevent the leakage of lead ions (the lead leakage inhibition rate is as high as 85%). BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Schematic diagram of the process of forming the perovskite light absorbing layer film prepared in Example 1 and Comparative Example 1;
[0018] Figure 2 The JV curves of the perovskite solar cells prepared in Example 1 and Comparative Example 1 are shown, wherein control is a standard sample and PFPA is a device modified with pentafluorophenol acrylate;
[0019] Figure 3 The stability dot-line diagram of the perovskite solar cell device prepared in Example 1 and Comparative Example 1, wherein control is a standard sample and PFPA is a device modified with pentafluorophenol acrylate;
[0020] Figure 4 X-ray diffraction patterns of the perovskite films prepared in Example 1 and Comparative Example 1;
[0021] Figure 5 Surface scanning electron microscope images of the perovskite films prepared in Example 1 and Comparative Example 1;
[0022] Figure 6 The lead ion content distribution diagram of the perovskite solar cell devices prepared in Example 1 and Comparative Example 1.
[0023] Figure 7 This is the H-NMR spectrum of pentafluorophenol acrylate before and after heating. DETAILED DESCRIPTION
[0024] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0025] Example 1: A perovskite solar cell modified with pentafluorophenol acrylate, comprising a fluorinated conductive glass substrate, an electron transport layer, a perovskite light absorbing layer, a hole transport layer and a metal electrode stacked in sequence. The specific preparation method comprises the following steps:
[0026] (1) Preparation of fluorinated conductive glass substrate: First, fluorinated tin oxide (FTO) glass was cleaned in an ultrasonic bath with detergent, deionized water, ethanol, acetone and isopropanol for 15 minutes in sequence, and then the FTO glass was dried and ozonated with ultraviolet light for 15 minutes before use.
[0027] (2) Preparation of electron hole transport layer: Take 80uL of diluted SnO2 aqueous solution (mass fraction of 15% SnO2: water = 1:3, v / v), spin coat it on the ozonated FTO glass at a speed of 4000rpm for 30s, then anneal at 150℃ for 30min, cool to room temperature and set aside.
[0028] (3) Preparation of perovskite light-absorbing layer modified with pentafluorophenol acrylate:
[0029] 548.6 mg of lead iodide, 77.07 mg of lead bromide, 190.12 mg of formamidine hydroiodide and 21.84 mg of methyl ammonium bromide were weighed and dissolved in 1 mL of DMF / DMSO (4:1, v / v) to prepare a precursor solution, and then 34 μL of CsI solution (519 mg of CsI dissolved in 1 mL of DMSO) was added and stirred for 2 h to obtain a perovskite precursor solution. 60 μL of the perovskite precursor solution was coated on the SnO2 film in two steps. The first step was to spin coat at 2200 rpm / min for 10 s, and the second step was to coat at 4500 rpm / min for 45 s. 15 s before the end of the second step of spin coating, 200 μL of a modified solution prepared by 3 mg of pentafluorophenol acrylate, 0.15 mg of azobisisobutyronitrile and 1 mL of chlorobenzene was added dropwise, and Cs was annealed at 110 ° C for 60 min to obtain the film. 0.05 MA 0.16 FA 0.79 Pb(I 0.83 Br 0.17 )3 perovskite light absorbing layer, the concentration of pentafluorophenol acrylate in the modified solution selected in this embodiment is 3 mg / mL. The schematic diagram of the process of pentafluorophenol acrylate modifying the perovskite light absorbing layer is as follows Figure 1 The results of H-NMR spectra of the acrylic acid pentafluorophenol ester before and after annealing polymerization are as follows: Figure 7 The results show that pentafluorophenol acrylate before heating contains three characteristic peaks of carbon-carbon double bond spectrum, while the three characteristic peaks of pentafluorophenol acrylate after heating completely disappear, indicating that the carbon-carbon double bond has been broken, a new product has been formed, and a polymerization reaction has occurred, indicating the formation of a polymer film.
[0030] (4) Preparation of hole transport layer: After the perovskite film was cooled to room temperature, 60 μL Spiro-OMeTAD solution was spin-coated on the top of the perovskite film at 4000 rpm for 20 s. The Spiro-OMeTAD solution consisted of 100 mg 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD), 21 μL lithium bis(trifluoromethanesulfonyl)imide solution (260 mg Li-TFSI containing 1 mL acetonitrile), 36 μL tributyl phosphate (t-BP) and 1 mL monochlorobenzene (CB).
[0031] (5) Metal electrode preparation: In a vacuum evaporator (1×10 -3 80 nm Au electrodes were deposited in 4% Pa.
[0032] The above steps (2, 3, 4) are all carried out by spin coating layer by layer using a coating machine.
[0033] Example 2: The difference between Example 2 and Example 1 is that the concentration of pentafluorophenol acrylate added in step (3) is 1 mg / mL.
[0034] Example 3: The difference between Example 3 and Example 1 is that the concentration of pentafluorophenol acrylate added in step (3) is 5 mg / mL.
[0035] Example 4: The difference between Example 4 and Example 1 is that the specific steps of step (3) are as follows: 1.5mmol PbI2, 1.5mmol formamidine hydroiodide (FAI) and 0.525mmol methyl ammonium chloride (MACl) are dissolved in 1mL The FAPbI3 perovskite precursor solution was obtained in a mixed solution of DMF:DMSO (volume ratio of 9:1), and then 60 μL of the perovskite precursor solution was spin-coated in a glove box filled with nitrogen. The first step was spin-coated at a speed of 2200 rpm / min for 10 s, and the second step was coated at a speed of 5000 rpm / min for 45 s. 10 s before the end of the second step of spin coating, 200 μL of a modified solution prepared by 3 mg of pentafluorophenol acrylate, 0.15 mg of azobisisobutyronitrile and 1 mL of chlorobenzene was spin-coated onto the SnO2 / FTO substrate, and annealed at 150°C for 10 min, and then annealed at 100°C for 10 min to obtain the perovskite titanium absorption layer.
[0036] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that step (3) is not modified with pentafluorophenol acrylate, and when the perovskite precursor solution is dripped onto the electron transport layer using the antisolvent titration method, the same volume of chlorobenzene antisolvent is titrated during the spin coating process, and the other steps are the same.
[0037] Comparative Example 2: The difference between Comparative Example 2 and Example 4 is that step (3) is not modified with pentafluorophenol acrylate, and when the perovskite precursor solution is dripped onto the electron transport layer by anti-solvent titration method, the same volume of chlorobenzene anti-solvent is titrated during the spin coating process, and the other steps are the same.
[0038] The performance of the perovskite solar cells prepared in Examples 1 to 3 and Comparative Examples 1 to 2 was tested, and the results were as follows:
[0039] (1) The light-to-heat conversion efficiency of the perovskite solar cells prepared in Example 1 and Comparative Example 1 was tested, and the JV curves thereof are shown in FIG. Figure 2 , where control represents the sample of comparative example 1, and PFPA represents the perovskite solar cell modified with pentafluorophenol acrylate prepared in Example 1. The results show that the perovskite solar cell device modified with pentafluorophenol acrylate can better improve the quality of the film, improve the transmission capacity of electrons, passivate defects, increase the life of carriers, and obtain a photoelectric conversion efficiency of 22.35%.
[0040] (2) The stability of the perovskite solar cells prepared in Example 1 and Comparative Example 1 was tested, and the results are as follows: Figure 3 , where control represents the sample of comparative example 1, and PFPA represents the perovskite solar cell modified with pentafluorophenol acrylate prepared in Example 1. It shows that the perovskite solar cell modified with pentafluorophenol acrylate has better hydrophobicity and stability. After being exposed to a dark environment with high humidity (RH=50±10%, T=25°C) for 1000 hours, the PCE retention rate of Example 1 is 87.0%, while the PCE retention rate of comparative example 1 is only 59.0%. Therefore, it can be preserved for a long time in the environment, laying a foundation for commercial development during the period.
[0041] (3) X-ray diffraction test was performed on the perovskite solar cell film prepared in Example 1. The results are as follows: Figure 4 The control film showed obvious non-perovskite phase PbI2 at 12.4°, indicating that the crystallinity of the perovskite film modified with pentafluorophenol acrylate was improved, the (110) crystal plane value at 14.2° was significantly improved, and the generation of PbI2 phase was significantly inhibited, and the quality of the perovskite film was improved.
[0042] (4) The morphology of the perovskite solar cells prepared in Example 1 and Comparative Example 1 was tested. The results are as follows: Figure 5 It shows that the surface of the perovskite film modified with pentafluorophenol acrylate is smoother, and the grains are significantly larger (from 310.87nm to 409.09nm), showing a highly ordered orientation, indicating that the introduction of pentafluorophenol acrylate helps the growth of perovskite particles, reduces grain boundaries, and also reduces the generation of defects, providing a basis for carrier transport.
[0043] (5) The lead ion content of the perovskite solar cells prepared in Example 1 and Comparative Example 1 was tested. The results are as follows Figure 6 , indicating that perovskite solar cells modified with pentafluorophenol acrylate are more environmentally friendly cells, reducing the risk of lead leakage in future practical applications and protecting the threat to the environment. The lead leakage inhibition rate is as high as about 85%.
[0044] (6) The photoelectric conversion efficiency of the devices prepared in Examples 1 to 3 and Comparative Examples 1 to 2 and the lead ion leakage concentration of the perovskite film in water were tested. The results are shown in Table 1: the photoelectric conversion efficiency of the perovskite solar cell modified with pentafluorophenol acrylate is significantly improved, and after being immersed in water for 2 hours, the lead ion concentration in the detected aqueous solution is the lowest, which effectively prevents the leakage of lead ions.
[0045] Table 1: Photoelectric conversion efficiency of devices prepared in Examples 1 to 3 and Comparative Examples 1 to 2 and lead ion leakage concentration of perovskite films in water.
[0046]
[0047] In summary, the preparation method of the perovskite solar cell based on pentafluorophenol acrylate modified by the present invention is simple in process. In the heat treatment process, pentafluorophenol acrylate and azobisisobutyronitrile initiator work together to cause in-situ self-polymerization. The generated polymer film passivates the defects of the perovskite, improves the quality of the perovskite film, effectively reduces the non-radiative recombination of carriers, and also promotes the extraction and transmission of carriers, thereby improving its photoelectric conversion efficiency; and forms a polymer cross-linked network wrapped on the perovskite grain boundary. During the perovskite crystal growth process, C=O in the molecule and uncoordinated Pb 2+ Combined with other materials, it can effectively prevent the leakage of lead ions.
[0048] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A perovskite solar cell modified with pentafluorophenol acrylate, comprising a fluorinated conductive glass substrate, an electron transport layer, a perovskite light absorbing layer, a hole transport layer and a metal electrode stacked in sequence, characterized in that: The perovskite light-absorbing layer is coated with a modified solution containing pentafluorophenol acrylate, azobisisobutyronitrile and an anti-solvent and then annealed.
2. A perovskite solar cell modified with pentafluorophenol acrylate according to claim 1, characterized in that: The concentration of pentafluorophenol olefinate in the modified solution is 3 mg / mL.
3. A perovskite solar cell modified with pentafluorophenol acrylate according to claim 1, characterized in that: The anti-solvent is one of chlorobenzene, isopropanol and ethyl acetate.
4. A method for preparing a perovskite solar cell modified with pentafluorophenol acrylate, characterized in that: The following steps are involved: (1) Preparation of fluorinated conductive glass substrate: A FTO glass substrate was cleaned with detergent, deionized water, acetone and isopropanol in sequence, then dried and treated with ozone; (2) Preparation of electron transport layer: coating a SnO2 precursor solution on a FTO glass substrate and annealing; (3) Perovskite light-absorbing layer: a perovskite precursor solution prepared with lead halide, formamidine hydroiodide and methyl ammonium bromide is spin-coated on the electron transport layer, and then a modified solution prepared with pentafluorophenol acrylate, azobisisobutyronitrile and anti-solvent is dropped in for spin-coating deposition to form a perovskite light-absorbing layer; (4) Hole transport layer: A 2,2',7,7'-tetrakis[n,n-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene solution is deposited on the perovskite light absorbing layer to obtain a hole transport layer. (5) Metal electrode: Au electrode with a thickness of 80-100 nm.
5. The method for preparing a perovskite solar cell modified by pentafluorophenol acrylate according to claim 4, wherein the lead halide comprises at least one of lead iodide and lead bromide.
6. The preparation method according to claim 3, characterized in that: The step (3) is specifically as follows: 548.6 mg of lead iodide, 77.07 mg of lead bromide, 190.12 mg of formamidine hydroiodide and 21.84 mg of methyl ammonium bromide are weighed and dissolved in DMF / DMSO to prepare a precursor solution, and then 34 μL of a 519 mg / mL CsI solution is added and stirred for 2 hours to obtain a perovskite precursor solution, and 60 μL of the perovskite precursor solution is coated on the SnO2 film in two steps, the first step is to spin coat at a speed of 2200 rpm / min for 10 seconds, and the second step is to coat at a speed of 4500 rpm / min for 45 seconds, and 15 seconds before the end of the second step of spin coating, 200 μL of a modified solution prepared by 3 mg of pentafluorophenol acrylate, 0.15 mg of azobisisobutyronitrile and 1 mL of chlorobenzene is dripped on the film, and annealed at 110° C. for 60 minutes to obtain a perovskite light absorbing layer.
7. The preparation method according to claim 3, characterized in that: The step (3) is specifically to dissolve 1.5mmol PbI2, 1.5mmol formamidine hydroiodide and 0.525mmol methyl ammonium chloride in a mixed solution of DMF:DMSO to obtain a perovskite precursor solution, then take 60μL of the perovskite precursor solution and perform two-step coating on the SnO2 film, the first step is to spin coat at a speed of 2200rpm / min for 10s, and the second step is to coat at a speed of 4500rpm / min for 45s, in the last 10s of the second step, take 200μL of a modified solution prepared by 3mg pentafluorophenol acrylate, 0.15mg azobisisobutyronitrile and 1mL chlorobenzene, spin coat and drop it on the film, first anneal at 150°C for 10min, and then anneal at 100°C for 10min to obtain a perovskite titanium light absorbing layer.
Citation Information
Patent Citations
Perovskite solar cell and preparation method thereof
CN115249771A
Perovskite quantum dot composite film and preparation method thereof
CN116001378A
Perovskite solar cell internal packaging method based on in-situ polymerization
CN119277937A